Coniferous Ovulate Cones from the Lower Cretaceous of Santa Cruz Province, Argentina - del Fueyo, Georgina Marisa (2008)
Two types of coniferous ovulate cones borne on leafy twigs are described from the Lower Cretaceous Kachaike Formation in Santa Cruz Province, Argentina. The fossils are impressions and compressions with well-preserved cuticles. Morphology, anatomy, and ultrastructure were studied using LM, SEM, and TEM. Ovulate cones were assigned to Athrotaxis ungeri (Halle) Florin of the taxodiaceous Cupressaceae and Kachaikestrobus acuminatus gen. et sp. nov. of the Cheirolepidiaceae. This latter taxon is characterized by terminal elongate cones borne on twigs with Brachyphyllum leaves, cone scales densely and helically disposed, broad bracts with an accentuated acuminate apex fused at their bases to eight-lobed ovuliferous dwarf shoots shorter than the bracts, and an epimatium covering at least one ovule that has preserved only the outer integument and the megaspore membrane. The ultrastructure of the bract and ovuliferous dwarf shoot cuticle is composed of three layers. Comparisons of K. acuminatus with other cheirolepidiaceous ovulate cones showed closest resemblance to Hirmeriella muensteri (Schenk) Jung. These Patagonian cone scales appear to have some of the most ancestral characters in the family. By the early Albian, A. ungeri and K. acuminatus were part of a plant assemblage dominated by ferns and a few subordinate angiosperms. The ﬁnding of A. ungeri in the Kachaike Formation extends its distribution during the Lower Cretaceous in Patagonia. These fossils also show that at that time, the taxodiaceaous Cupressaceae and the Cheirolepidiaceae still were well represented in southern South America.